Teaming behavior in adversarial scenarios - Shishika, Daigo; Dorothy, Michael; Macharet, Douglas G. (Frontiers in Control Engineering, 2023)
Interesting and effective team behaviors arise when a group of agents contend with adversaries.Examples range from animal group behaviors observed in nature to strategies used in team sports. This mini review goes over literature in multiagent systems that study group control in adversarial scenarios. We identify different ways of formulating adversaries and discuss various types of teaming behavior that arise. Specifically from the perspective of multiagent task assignment, the types of tasks and the nature of assignments brought by the adversary are categorized. The frontiers of the current literature and the direction for future research are discussed at the end.